PENGARUH MODEL PEMBELAJARAN BRAINWRITING TERHADAP KETERAMPILAN MENULIS SISWA KELAS III SD - Harefa, Melinna; Faisal, F; Lubis, Wildansyah; Simanjuntak, Eva Betty; Sembiring, Masta Marselina (Jurnal Merah Putih Sekolah Dasar, 2024)
This research aims to determine the effect of the Brainwriting learning model on the writing skills of class III students at SDN 060857 Kec. Medan Tembung T.A 2023/2024. This type of research is quasi-experimental research using the Quasi Experimental Design method where class III-A is the experimental class and class III-B is the control class. The subjects in this research consisted of two classes, namely class III-A totaling 25 students and class III-B totaling 23 students. Data collection techniques in this research are interviews, observation, questionnaires, and tests. In the pre-test results, the experimental class got an average of 55.6 and the control class 53.9. Then the experimental class was given treatment using the Brainwriting learning model and got a post-test average of 87.8, while the control class was not given treatment and got a post-test average of 80.2. From these results it can be concluded that there is an influence of the Brainwriting learning model on students' writing skills in Theme 5 Weather Sub Theme 2 Changes in Weather Learning 2 class III SDN 060857 Kec. Medan Tembung.   Keywords: Brainwriting, Writing Skills